Gender and Low Albumin and Oxygen Levels are Risk Factors for Perioperative Pneumonia in Geriatric Hip Fracture Patients - Wang X (Dove Medical Press, 2020)
Xiaoyan Wang,1 Li Dai,1 Yunjian Zhang,1 Yanwei Lv2 1Department of Respiratory Medicine, Beijing Jishuitan Hospital, Beijing, People’s Republic of China; 2Clinical Epidemiology Research Center, Beijing Jishuitan Hospital, Beijing, People’s Republic of ChinaCorrespondence: Xiaoyan Wang Email wang_wxy@163.comIntroduction: Pneumonia is a serious complication following hip fracture and is the primary risk factor for 30-day mortality after surgery. Modifying several laboratory factors may improve the outcomes of fragile hip fracture patients who are 80 years or older.Purpose: To investigate several adjustable factors for perioperative pneumonia in order to improve patient prognosis and reduce mortality.Patients and Methods: We retrospectively reviewed in-hospital hip fracture data from patients who were 80 years or over between January 1, 2014, and November 31, 2014, from Beijing Jishuitan Hospital. Patients were divided into two groups: perioperative pneumonia (POP) group and non-perioperative pneumonia (non-POP) group. Logistic regression models were used to identify independent risk factors. Statistical significance was set at 5% (p< 0.05).Results: The incidence of perioperative pneumonia (POP) in patients 80 years and older was 11.3% (33/293). Male patients had a higher incidence of POP (20/96 cases, 20.83%) compared to females (13/197, 6.6%)(P< 0.001). Higher neutrophilic granulocyte percentages (78.148%± 9.162% in POP vs 81.959%± 6.142% in Non-POP, P=0.033) and lower albumin levels (χ2=2.25, P=0.039) were observed in the POP group at baseline. After multivariate logistic regression, we observed that males (OR=3.402, P=0.048), lower albumin levels (OR=10.16, P=0.001) and PaO2 levels (OR=2.916, P=0.007) were independent risk factors for POP.Conclusion: Low albumin and oxygen levels and the male gender were risk factors for perioperative pneumonia in geriatric hip fracture patients.Keywords: hip fracture, pneumonia, elderly, perioperative, male, hypoalbuminemia, arterial blood gas analysis